The influence of selected environmental factors on the time of natural menopause in women living in the Małopolskie voivodeship - Szwejser, Ewa; Szostek, Krzysztof (Anthropological Review, 2012)
The main objective of the study is to determine which of the chosen environmental factors and selected groups of such factors alter the time of natural menopause in women living in the Małopolska region. Two hundred and thirty two women aged over 40 years were investigated in a cross-sectional survey in Cracow and the surrounding area. Among them 165 women who had undergone natural menopause and had their last bleeding at least 12 month prior to the interview were chosen. To estimate the age at menopause, a retrospective method was used. Univariate and multivariate methods were employed to estimate association of age at natural menopause with factors of interest. Mean age at natural menopause was 50.32 years (SD=3.82). Among biological and socio-economic factors, only the length of the reproductive period (H=106.07; p=0.000) and the age at the time of the first birth (R=0.18; p=0.020) turned out to be associated with the age at natural menopause in the studied group. The length of the smoking period (R=–0.17; p=0.031), the amount (F=3.25; p=0.04) and frequency of alcohol consumed (H=6.95; p=0.031) were the environmental factors related to the time of menopause. Women who drank more and smoked over longer period of time were likely to experience menopause earlier than their less drinking and shorter smoked counterparts. Three factors taken together, frequency of smoking, alcoholic intake and the age the tobacco addiction started (F=3.87; p=0.050), as well as the consumption of strong alcoholic drinks and the early start of tobacco addiction (F=2.85; p=0.026) were significantly related to the occurrence of natural menopause.